INCREASING TOEFL SCORE USING MIND MAPPING METHOD - Evan Afri; Muhammad Khoiruddin Harahap (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
English which is an international language has become an important requirement in the world of education. Standardization of English proficiency is measured by a TOEFL score in stages. Especially for students who are looking for scholarships at home and abroad, making the TOEFL score is a major requirement. International scholarships require a minimum TOEFL score of 550. This study is concerned with Mind Mapping strategies or techniques which  can improve TOEFL scores. The implementation of this method is carried out for active students of Ganesha Polytechnic as a research sample through two stages, namely Pre-Test, and Final-Test. The number of samples used in this study is as many as 300 students consisting of semester 1, semester 3 and semester. Based on the results of trials with the Mind Mapping method with a duration of 3 months there is an increase in the TOEFL score between Pre-Test and Final Test.